Ultrasound guided regional anesthesia - Grant, Stuart A.; Auyong, David B. (Oxford University Press, 2017)
This book provides a detailed, stepwise approach to performing ultrasound guided regional anesthesia, identifying pearls and pitfalls to ensure success. Basic principles are covered, followed by techniques for upper extremity, lower extremity, and chest, trunk and spine nerve blocks. Each nerve block is comprehensively explained, divided up by introduction, anatomy, clinical applications, technique, alternate techniques, complications, and pearls.